2001
DOI: 10.1111/j.1749-6632.2001.tb04028.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selective Estrogen Receptor Modulators on Reproductive Tissues Other Than Endometrium

Abstract: The objective of this paper is to review the published and unpublished knowledge of the effect of selective estrogen receptor modulators on reproductive tissues other than endometrium. Pharmaceutical companies developing or marketing selective estrogen receptor modulators (SERMs) were identified. The investigators at each company responsible for the conduct of investigational trials were contacted and queried about reports of adverse events in any ongoing or completed trials involving SERMs produced by their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 26 publications
1
17
0
1
Order By: Relevance
“…Since both estrogen receptors, ERa and ERb, are present in the vesico-vaginal and recto-vaginal fascias, it is possible to modulate the expression of ERs by either the estrogens or the selective estrogen receptor modulators. SERMs such as levormeloxifene and idoxifene, increase the risk of pelvic organ relaxation and POP was reported to the American Food and Drug Administration (FDA) as an adverse event associated with both drugs [9,10]. Current analysis, based on data obtained from post-menopausal women treated with raloxifene, demonstrates that raloxifene was associated with a 50% reduction in the risk of surgery for pelvic floor relaxation in women treated for up to three years [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since both estrogen receptors, ERa and ERb, are present in the vesico-vaginal and recto-vaginal fascias, it is possible to modulate the expression of ERs by either the estrogens or the selective estrogen receptor modulators. SERMs such as levormeloxifene and idoxifene, increase the risk of pelvic organ relaxation and POP was reported to the American Food and Drug Administration (FDA) as an adverse event associated with both drugs [9,10]. Current analysis, based on data obtained from post-menopausal women treated with raloxifene, demonstrates that raloxifene was associated with a 50% reduction in the risk of surgery for pelvic floor relaxation in women treated for up to three years [8].…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, the protective influence of raloxifene on the development of POP after nine months of therapy and a 50% reduction of the surgical intervention risk in post-menopausal women have been reported [8]. Furthermore, SERMs such as levormeloxifene and idoxifene have been found to increase the risk of pelvic organ prolapse and POP was reported as an adverse event associated with both drugs [9,10].…”
mentioning
confidence: 99%
“…Clinical data show that up to 5 years of adjuvant tamoxifen treatment substantially improves 10-year survival in women with hormone receptor-positive (HRþ) or receptor-unknown early breast cancer [2]. However, about 30% of women complain of side-effects including hot flashes, vaginal discharge, and vaginal bleeding [3,4]. Tamoxifen treatment is also associated with a higher risk of less common, but much more serious, long-term side-effects; studies have found a two to four times higher relative risk of developing endometrial cancer in women taking tamoxifen than in agematched populations [5,6].…”
Section: Tamoxifen Its Predecessors and Its Successorsmentioning
confidence: 99%
“…Les ratios traités/témoins à quatre ans étaient respectivement de 1,5 pour l'incontinence avec hyperactivité vésicale et 1,7 pour l'incontinence à l'effort, ce qui indiquait une fréquence accrue Deux études reportent enfin les effets sur la continence des modulateurs sélectifs des récepteurs estrogéniques. Dans les essais portant sur l'administration du levormeloxifene, il est reporté une augmentation par quatre de l'incidence de l'incontinence urinaire [51] et de l'absence de bénéfice sous raloxifène [52].…”
Section: Traitements Médicamenteuxunclassified